Digital LKPD with Educandy on Neighborhood Topic in Elementary School - Tazkia, A'Shoka Najma; Irdiyansyah, Iyan; Destiana, Dita (Institut Darul Falah Bandung Barat, 2025)
Development of a Digital Student Worksheet (LKPD) using the Educandy application. This research aims to enhance the learning experiences of fourth-grade students. The study involved 28 participants and assessed the effectiveness of the LKPD on the topic